2019
DOI: 10.1111/jfd.13061
|View full text |Cite
|
Sign up to set email alerts
|

A new potential therapeutic remedy against Aeromonas hydrophila infection in rainbow trout (Oncorhynchus mykiss) using tetra, Cotinus coggygria

Abstract: Different antibiotic‐based drugs are being used for the treatment of Aeromonas hydrophila infection in rainbow trout, and several studies emphasize the use of medicinal plants as immunostimulants for prophylactic measure against Aeromoniasis disease. However, therapeutic effects of aqueous methanolic extracts of tetra (Cotinus coggygria) against A. hydrophila in rainbow trout were not investigated. Four different concentrations of tetra extract (0 [control], 4, 8 and 12 mg/100 µl) and also two different positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Moreover, IL-10 gene expression level was significantly increased in rainbow trout after tetra administration (Bilen & Elbeshti, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, IL-10 gene expression level was significantly increased in rainbow trout after tetra administration (Bilen & Elbeshti, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…(2019) reported an enhanced IL‐10 gene expression in rainbow trout fed with U. barbata extract. Moreover, IL‐10 gene expression level was significantly increased in rainbow trout after tetra administration (Bilen & Elbeshti, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, herbal‐derived immunostimulants have been widely used to enhance immunity in fish (Bilen & Elbeshti, 2019; Bilen et al, 2019; Bulfon et al, 2015; Hajirezaee et al, 2019; Rafieepour et al, 2019; Van Hai, 2015). Among these studies, some studies have also reported the effect of plant‐derived substances on prevention and modification of bacterial infections in fish (Divyagnaneswari et al, 2008; Ponnusamy et al, 2010; Sharma et al, 2010; Sivaram et al, 2004).…”
Section: Introductionmentioning
confidence: 99%